Structural Prediction Model Satisfaction and Buying Decision of Muslim Consumers Towards Fast Food by Halal Labeling - I Gusti Bagus Rai Utama, Intan Nurrachmia, Setiawan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This exploration means to comprehend what impacts Muslims in Bandung in creation choices on purchasing inexpensive food. The objects of this exploration are Muslim cheap food customers in Bandung. Information was gathered through an overview utilizing polls as a helping instrument. There were 180 respondents as tests. The information examination was led utilizing Structural Equation Modeling – Partial Least Square (SEM–PLS) approach. The exploration results show that the halal logo has a positive and critical impact on purchasing choices and that the clients' fulfillment likewise has a positive and huge effect on purchasing choices. Moreover, buyers' fulfillment can intervene in the impact of the halal logo on purchasing choices. This examination result is relied upon to urge eatery supervisors to be more mindful of the significance of the halal logo on their items.